The Efforts of Islamic Religious Education Teachers and Characteristics in Improving Students' Learning Interest - Muhammad Suyudi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This research was motivated by the low interest in student learning in Islamic Religious Education and Character, especially at SDN Mundu 1. This study used a qualitative field method. Data collection techniques used are observation, interviews, and documentation. Meanwhile, the data analysis technique used an interpretive descriptive approach. The results of this study are (1) The teacher's efforts include: The teacher always pays attention to students who have less interest in learning, provides measurable homework, the Teacher must always provide motivation to students and use more varied learning methods; (2) Supporting factors include: adequate school facilities and infrastructure, applying the PAIKEM learning method, a safe and comfortable school environment; (3) Inhibiting factors include: students feeling lazy to learn, lack of teacher and lack of support from students' parents; (4) The solution is to add school facilities such as labs and libraries, provide motivation to students, increase the number of teachers, and provide homework.